Efficacy and safety of endoscopic resection of large colorectal polyps: a systematic review and meta-analysis. Issue 5 (13th February 2015) - Hassan, C; Repici, A; Sharma, P; Correale, L; Zullo, A; Bretthauer, M; Senore, C; Spada, C; Bellisario, Cristina; Bhandari, P; Rex, D K
Abstract : Objective: To assess the efficacy and safety of endoscopic resection of large colorectal polyps. Design: Relevant publications were identified in MEDLINE/EMBASE/Cochrane Central Register for the period 1966–2014. Studies in which ≥20 mm colorectal neoplastic lesions were treated with endoscopic resection were included. Rates of postendoscopic resection surgery due to non-curative resection or adverse events, as well as the rates of complete endoscopic removal, invasive cancer, adverse events, recurrence and mortality, were extracted. Study quality was ascertained according to Newcastle-Ottawa Scale. Forest plot was produced based on random effect models. I 2 statistic was used to describe the variation across studies due to heterogeneity. Meta-regression analysis was also performed. Results: 50 studies including 6442 patients and 6779 large polyps were included in the analyses. Overall, 503 out of 6442 patients (pooled rate: 8%, 95% CI 7% to 10%, I 2 =78.6%) underwent surgery due to non-curative endoscopic resection, and 31/6442 (pooled rate: 1%, 95% CI 0.7% to 1.4%, I 2 =0%) to adverse events. Invasive cancer at histology, non-curative endoscopic resection, synchronous lesions and recurrence accounted for 58%, 28%, 2.2% and 5.9% of all the surgeries, respectively. Endoscopic perforation occurred in 96/6595 (1.5%, 95% CI 1.2% to 1.7%) polyps, while bleeding in 423/6474 (6.5%, 95% CI 5.9% to 7.1%). Overall, 5334 patients entered in surveillance, 502/5836 (8.6%, 95% CI 7.9% to 9.3%) being lost at follow-up. Endoscopic recurrence was detected in 735/5334 patients (13.8%, 95% CI 12.9% to 14.7%), being an invasive cancer in 14/5334 (0.3%, 95% CI 0.1% to 0.4%). Endoscopic treatment was successful in 664/735 cases (90.3%, 95% CI 88.2% to 92.5%). Mortality related with management of large polyps was reported in 5/6278 cases (0.08%, 95% CI 0.01% to 0.15%). Conclusions: Endoscopic resection of large polyps appeared to be an extremely effective and safe intervention. However, an adequate endoscopic surveillance is necessary for its long-term efficacy.